2022
DOI: 10.1007/s13399-022-03299-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel nano-biosorbent materials from thermal catalytic degradation of green pea waste for cationic and anionic dye decolorization

Abstract: The recycling of waste materials in wastewater decontamination has been an attractive discipline in zero discharge and energy recovery. Biochar/zeolite nanocomposite has been successfully synthesized as a cheap and eco-friendly material from a solid fraction obtained from the thermos-catalytic conversion of green pea agriculture waste (Pisum sativum). A dark-whitish solid was obtained from thermal pyrolysis at 450 °C with a heating rate of 27 °C/min for 15 min that was further subjected to alkaline chemical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The BC pore size distribution in Figure 3 ranged from mesoporous to macroporous. The suited BC applications are in the following modes: mesoporous for pollutant decontamination and catalyst supports, microporous for nutrient retention in the soil, and macroporous for aeration of the soil [6]. The N 2 adsorption and desorption studies of the BC are revealed in Figure 3.…”
Section: Bc's Surface Area and Pore Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The BC pore size distribution in Figure 3 ranged from mesoporous to macroporous. The suited BC applications are in the following modes: mesoporous for pollutant decontamination and catalyst supports, microporous for nutrient retention in the soil, and macroporous for aeration of the soil [6]. The N 2 adsorption and desorption studies of the BC are revealed in Figure 3.…”
Section: Bc's Surface Area and Pore Propertiesmentioning
confidence: 99%
“…Proc. 2023, 37, 77 2 of 7 to obtain pyrolysis products, such as bio-oil, syngas, and biochar [6]. This process involves heating biomass from ambient to peak temperature and holding it at that temperature for the required residence time in anoxic conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…These organic dyes have toxic, teratogenic, carcinogenic and mutagenic effects in living things. To prevent these problems, various methods such as adsorption, filtration, microbial‐based process, photocatalysis, phytoextraction, reverse osmosis, electrolysis and oxidation are used today [27–30] . These methods have disadvantages such as high cost, high energy and time consumption, and low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent these problems, various methods such as adsorption, filtration, microbial-based process, photocatalysis, phytoextraction, reverse osmosis, electrolysis and oxidation are used today. [27][28][29][30] These methods have disadvantages such as high cost, high energy and time consumption, and low productivity. In order to overcome these disadvantages, intensive studies are being carried out to develop various new materials such as protein-inorganic hybrid nanoflowers, metal nanoparticle, metal organic framework, nanosheet, nanocomposite etc.…”
Section: Introductionmentioning
confidence: 99%